Brand placement on price boards after tobacco display bans: a point-of-sale audit in Melbourne, Australia. Issue 6 (22nd September 2012) - Wakefield, Melanie; Zacher, Meghan; Scollo, Michelle; Durkin, Sarah
Abstract : Objective: This study aims to explore how cigarette brands are arranged on boards listing tobacco products and/or prices following the 1 January 2011 ban on point-of-sale tobacco displays in Victoria, Australia. Methods: An audit undertaken in late 2011 gathered information on the prevalence and contents of tobacco product information displays ('price boards'). We examined how often all or most of the brands listed at the top of price boards were owned by the same tobacco company, and whether premium, mainstream and value brands were listed in prominent positions more frequently in different store types and socio-economic areas (SES). Results: Of the 281 stores audited, 64% (179) had legible price boards. Of the 178 with factory-made products, 11% arranged brands alphabetically, 2% by price and 87% did so in some other way. In 65% of stores where brands were arranged in some other way, at least three of the top four positions were devoted to brands owned by the same tobacco company. Premium brands were given greater prominence than would be expected by market share. Neighbourhood SES was significantly related to the representation in the most prominent price board positions of brands from the most appropriate market segment. Conclusions: Price boards are being used to target brands to consumers. Jurisdictions should also prohibit price board display when they ban tobacco product display; prices might instead be itemised in alphabetical order on a list only viewable upon customer request.